2015
DOI: 10.1007/s00167-014-3488-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolated popliteus tendon injury does not lead to abnormal laxity in posterior-stabilised total knee arthroplasty

Abstract: These findings support the view that certain current designs of PS knee replacement can constrain the knee in flexion in the absence of postero-lateral deficiency. For this implant, isolated sectioning of the popliteus tendon did not substantially generate abnormal knee laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Our described technique, in the correct patient, offers relief of symptoms 1 without compromising knee stability. 8 The role of the popliteal tendon in knee stability continues to be debated. Although we know the structure is important in native knees, 9 its role in knee stability after arthroplasty is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our described technique, in the correct patient, offers relief of symptoms 1 without compromising knee stability. 8 The role of the popliteal tendon in knee stability continues to be debated. Although we know the structure is important in native knees, 9 its role in knee stability after arthroplasty is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaveric study, resection of the popliteal tendon was not associated with knee instability in posteriorstabilized (PS) TKA implants. 8 For these reasons, resection of the popliteal tendon after TKA with PS implants may be considered safe. An alternative treatment for popliteal dysfunction in TKA would be to address the impinging lesion by either resecting the osteophyte 5 or revising the femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…PS prostheses may prevent some rare TKA complications, such as luxation [11], by withstanding the more stress at the PS post. By using the PS-Triathlon as previously described [10], sectioning of the popliteal tendon in our study produced excellent results and did not generate adverse effects over 3 postoperative years.…”
Section: Discussionmentioning
confidence: 60%
“…They also speculated that the popliteus might not have the same critical functions after TKA because of the combination of increased constraint in the TKA relative to the native knee and the relatively lower functional demand in this patient population. In addition, a recent experimental study [10] using the current constrained design of the PS knee replacement (PS-Triathlon) revealed that isolated sectioning of the popliteal tendon did not substantially generate abnormal knee laxity to 90° during knee flexion. PS prostheses may prevent some rare TKA complications, such as luxation [11], by withstanding the more stress at the PS post.…”
Section: Discussionmentioning
confidence: 99%
“…Popliteus tendon damage has been reported in the literature with conventional knee replacements, but probably innocuous to patients [80] and also insignificant on knee laxity in particular [81]. As a result, we could consider this complication as minor, whereas the patella tendon rupture is unquestionably more serious as well as deep peroneal nerve injury which have both severe consequences and sometimes definitive impairment for patients.…”
Section: Potential Limitations Of Mismentioning
confidence: 99%